Health Benefits of Consuming Foods with Bacterial Probiotics, Postbiotics, and Their Metabolites: A Review - Victor E. Vera-Santander; Ricardo H. Hernández-Figueroa; María T. Jiménez-Munguía; Emma Mani-López; Aurelio López-Malo (Molecules, 2023)
Over the years, probiotics have been extensively studied within the medical, pharmaceutical, and food fields, as it has been revealed that these microorganisms can provide health benefits from their consumption. Bacterial probiotics comprise species derived from lactic acid bacteria (LAB) (genus Lactobacillus, Leuconostoc, and Streptococcus), the genus Bifidobacterium, and strains of Bacillus and Escherichia coli, among others. The consumption of probiotic products is increasing due to the current situation derived from the pandemic caused by COVID-19. Foods with bacterial probiotics and postbiotics are premised on being healthier than those not incorporated with them. This review aims to present a bibliographic compilation related to the incorporation of bacterial probiotics in food and to demonstrate through in vitro and in vivo studies or clinical trials the health benefits obtained with their metabolites and the consumption of foods with bacterial probiotics/postbiotics. The health benefits that have been reported include effects on the digestive tract, metabolism, antioxidant, anti-inflammatory, anticancer, and psychobiotic properties, among others. Therefore, developing food products with bacterial probiotics and postbiotics is a great opportunity for research in food science, medicine, and nutrition, as well as in the food industry.